Widespread Use of Migratory Megafauna for Aquatic Wild Meat in the Tropics and Subtropics - Ingram, Daniel J.; Prideaux, Margi; Hodgins, Nicola K.; Frisch-Nwakanma, Heidrun; Avila, Isabel C.; Collins, Tim; Cosentino, Mel; Keith-Diagne, Lucy W.; Marsh, Helene; Shirley, Matthew H.; Van Waerebeek, Koen; Djondo, Maximin K.; et al. (Frontiers in Marine Science, 2022)
Wild animals are captured or taken opportunistically, and the meat, body parts, and/or eggs are consumed for local subsistence or used for traditional purposes to some extent across most of the world, particularly in the tropics and subtropics. The consumption of aquatic animals is widespread, in some places has been sustained for millennia, and can be an important source of nutrition, income, and cultural identity to communities. Yet, economic opportunities to exploit wildlife at higher levels have led to unsustainable exploitation of some species. In the literature, there has been limited focus on the exploitation of aquatic non-fish animals for food and other purposes. Understanding the scope and potential threat of aquatic wild meat exploitation is an important first step toward appropriate inclusion on the international policy and conservation management agenda. Here, we conduct a review of the literature, and present an overview of the contemporary use of aquatic megafauna (cetaceans, sirenians, chelonians, and crocodylians) in the global tropics and subtropics, for species listed on the Appendices of the Convention on the Conservation of Migratory Species of Wild Animals (CMS). We find that consumption of aquatic megafauna is widespread in coastal regions, although to varying degrees, and that some species are likely to be at risk from overexploitation, particularly riverine megafauna. Finally, we provide recommendations for CMS in the context of the mandate of the Aquatic Wild Meat Working Group.